2010
DOI: 10.2337/dc10-1420
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure and Cardiovascular Disease Risk in the Veterans Affairs Diabetes Trial

Abstract: OBJECTIVEBlood pressure ranges associated with cardiovascular disease (CVD) events in advanced type 2 diabetes are not clear. Our objective was to determine whether baseline and follow-up (On-Study) systolic blood pressure (SBP), diastolic blood pressure (DBP), and SBP combined with DBP predict CVD events in the Veterans Affairs Diabetes Trial (VADT).RESEARCH DESIGN AND METHODSParticipants in the VADT (n = 1,791) with hypertension received stepped treatment to maintain blood pressure below the target of 130/80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 15 publications
3
55
0
2
Order By: Relevance
“…Moreover, glycaemic goals were more often achieved by patients in the older subgroups regardless the presence of a CVD, in accordance with the results from clinical trials and observational studies suggesting that a global control of cardiovascular risk factors in older patients provides a greater benefit regarding morbidity and mortality than an intensive glycaemic control 13, 14, 15, 16, 17. Antihypertensive treatment, for instance, has benefits even in very old patients 18, 19, 20, 21, and there are also compelling evidences of the benefit of statins and antiplatelet agents in older adults in secondary prevention of CVD, while its use in primary prevention is controversial, and individual characteristics and the risk of related adverse events should be taken into account 5, 7, 22, 23, 24, 25.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, glycaemic goals were more often achieved by patients in the older subgroups regardless the presence of a CVD, in accordance with the results from clinical trials and observational studies suggesting that a global control of cardiovascular risk factors in older patients provides a greater benefit regarding morbidity and mortality than an intensive glycaemic control 13, 14, 15, 16, 17. Antihypertensive treatment, for instance, has benefits even in very old patients 18, 19, 20, 21, and there are also compelling evidences of the benefit of statins and antiplatelet agents in older adults in secondary prevention of CVD, while its use in primary prevention is controversial, and individual characteristics and the risk of related adverse events should be taken into account 5, 7, 22, 23, 24, 25.…”
Section: Discussionsupporting
confidence: 83%
“…Also, in a subgroup analysis of participants with diabetes and coronary artery disease in the International Verapamil SR-Trandolapril (INVEST) study, tight control of SBP (≤130 mmHg) was not associated with improved cardiovascular outcomes compared with conventional BP control (130-140 mmHg), and a non-significant increase in the rate of allcause mortality was noted with tight BP control [11]. A J-shaped relationship was found in the Veterans Affairs Diabetes Trial (VADT), in which a higher risk of CVEs was found in patients with SBP ≥140 mmHg and DBP <70 mmHg [13].…”
Section: Discussionmentioning
confidence: 86%
“…In addition, other studies have shown an increase in the risk of CVEs and mortality when SBP is reduced to below 120 mmHg [11,12]. A diastolic BP (DBP) of <70 mmHg at baseline and during follow-up has been associated with a significantly increased risk of CVD [13].…”
Section: Introductionmentioning
confidence: 99%
“…45,46 Furthermore, a low diastolic blood pressure of <70 mm Hg that may result from SBP reduction is associated with higher cardiovascular disease risk. 42 Thus, the recommended target blood pressure for older diabetic patients is <140/90 mm Hg, if tolerated. 2 Lipid lowering by statins has been shown to reduce the incidents of major vascular events by approximately 20% per mmol/L low-density lipoprotein cholesterol reduction in diabetic patients and in patients age ≥65 years.…”
Section: Co-morbidities and Other Cardiovascular Risk Factorsmentioning
confidence: 99%
“…Systolic blood pressure (SBP) of ≥140 mm Hg increases the risk of cardiovascular events, whereas lowering blood pressure from a high level reduces both cardiovascular and microvascular complications in older diabetic patients. [42][43][44] There is no further benefit to lowering SBP to <130 mm Hg however, as compared to SBP of 130-140 mm Hg, but may increase mortality. 45,46 Furthermore, a low diastolic blood pressure of <70 mm Hg that may result from SBP reduction is associated with higher cardiovascular disease risk.…”
Section: Co-morbidities and Other Cardiovascular Risk Factorsmentioning
confidence: 99%